Correlations between the Market Price of Interest Rate Risk and Bond Yields - Yasuoka, Takashi (Journal of Reviews on Global Economics, 2017)
This paper examines empirical properties of the market price of interest rate risk, focusing on the relation between the price and interest rates. We briefly summarize how the market price of risk is estimated, and introduce the positive slope model to explain our empirical observation. The market price of risk is estimated for the U.S. Treasury market, 1970-2014, using the Hull–White model. We test the correlation between the market price of interest rate risk and bond yields. The results are that the yield change and term spreads are significantly correlated with the market price of risk, but the initial yields are not correlated with that. These results are theoretically interpreted by a mathematical model, and serve as a valuable reference for risk management as well as for study of financial policy.